What drives people to play pickleball? A mixed-methods study using SEM and fsQCA - Huang, Wenzhe; Xiao, Duxiang; Cheng, Bojin (Frontiers in Psychology, 2026)
IntroductionThis study aims to elucidate the pathways through which behavioral intention for pickleball participation is formed among the general public (i.e., individuals excluding professional or competitive athletes) and to analyze the decision-making mechanisms underlying participation.MethodsGrounded in the Theory of Planned Behavior (TPB), this research introduces exercise motivation as an antecedent variable. Based on a survey of 315 pickleball participants, it employs a mixed-methods approach combining Structural Equation Modeling (SEM) and fuzzy-set Qualitative Comparative Analysis (fsQCA) to empirically examine the influencing factors, pathways, and causal configurations of participation intention.Results(1) Exercise motivation significantly and positively influences behavioral intention; (2) Attitude and perceived behavioral control fully mediate the relationship between exercise motivation and behavioral intention, whereas the mediating role of subjective norm is not significant; (3) The inclusion of exercise motivation effectively enhances the explanatory power of the extended TPB model in predicting behavioral intention; (4) fsQCA identifies two distinct configurations sufficient for triggering high behavioral intention, with a positive attitude serving as a core condition in both.DiscussionThis study broadens the application boundaries of TPB in the context of sports participation and enriches the research on the psychological mechanisms of public participation in pickleball. Using the case of China, it provides theoretical support and practical guidance for promoting and popularizing pickleball in regions where the sport is in its early stages of development.